2017
DOI: 10.1038/srep44669
|View full text |Cite
|
Sign up to set email alerts
|

Social contagions on interdependent lattice networks

Abstract: Although an increasing amount of research is being done on the dynamical processes on interdependent spatial networks, knowledge of how interdependent spatial networks influence the dynamics of social contagion in them is sparse. Here we present a novel non-Markovian social contagion model on interdependent spatial networks composed of two identical two-dimensional lattices. We compare the dynamics of social contagion on networks with different fractions of dependency links and find that the density of final r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The first direction investigates how complex contagions spread within large networks of varying topologies. To date, researchers have examined threshold-based contagion models within power-law , locally tree-like (Gleeson and Cahalane 2007), degree-correlated (Gleeson 2008;Dodds and Payne 2009), directed (Gai and Kapadia 2010), weighted (Hurd and Gleeson 2013), small-world ), modular (Galstyan and Cohen 2007), clustered (Ikeda et al 2010;Hackett et al 2011), temporal (Karimi et al 2013;Backlund et al 2014), multiplex (Brummitt et al 2012;Yağan et al 2012, Lee et al 2014, and interdependent lattice networks (Shu et al 2017). Researchers have used different topologies to simulate how external factors like mass media influence cascade dynamics (Bassett et al 2012), and how topologies influence percolation processes (Zhao et al 2013).…”
Section: Theoretical Advancesmentioning
confidence: 99%
“…The first direction investigates how complex contagions spread within large networks of varying topologies. To date, researchers have examined threshold-based contagion models within power-law , locally tree-like (Gleeson and Cahalane 2007), degree-correlated (Gleeson 2008;Dodds and Payne 2009), directed (Gai and Kapadia 2010), weighted (Hurd and Gleeson 2013), small-world ), modular (Galstyan and Cohen 2007), clustered (Ikeda et al 2010;Hackett et al 2011), temporal (Karimi et al 2013;Backlund et al 2014), multiplex (Brummitt et al 2012;Yağan et al 2012, Lee et al 2014, and interdependent lattice networks (Shu et al 2017). Researchers have used different topologies to simulate how external factors like mass media influence cascade dynamics (Bassett et al 2012), and how topologies influence percolation processes (Zhao et al 2013).…”
Section: Theoretical Advancesmentioning
confidence: 99%
“…These models were then extended to study social contagions, particularly interacting, antagonistic contagions [31][32][33], and their cascading behaviors on multiplex networks [34][35][36][37]. Shu et al [38] present the dynamics of social contagions on two interdependent two-dimensional lattices, and give examples of nodes in communication networks which are spatially embedded [39][40][41]. Li et al [42] use a similar set-up to study the spread of epidemics, where they first pair two interconnected lattices, then pair two Erdős-Rényi (ER) networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, research has shown the importance of topological features, such as collective influence by degree [20], stochasticity and noise [21], and strategy/topology coevolution [22]. Shu et al [23] study contagions on two interdependent lattices, which are spatially constrained.…”
Section: Introductionmentioning
confidence: 99%